2020
DOI: 10.1155/2020/7624267
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Risk Factors and Self-Care Behaviors of Foot Ulceration in Diabetic Patients Attending Primary Healthcare Services in Palestine

Abstract: The purpose of this study is to identify certain sociodemographic, lifestyle, self-care, and foot examination factors that predict the development of diabetic foot ulcers in Palestine. A case-control study was performed in Palestine in 2019. The control group consisted of diabetic patients without foot ulceration (NFU). The case group included diabetic patients who had foot ulcers (DFU) with a size not less than 0.5 cm2. The sample of patients was taken from primary healthcare diabetic clinics in Palestine. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…A Palestinian study performed in 2019 demonstrated that smoking, sensory loss to vibration, sensory loss to monofilament, loss of pedal pulse, presence of calluses, nephropathy, retinopathy, neuropathy, and poor self-care behaviors were associated with DFU [4].…”
Section: Introductionmentioning
confidence: 99%
“…A Palestinian study performed in 2019 demonstrated that smoking, sensory loss to vibration, sensory loss to monofilament, loss of pedal pulse, presence of calluses, nephropathy, retinopathy, neuropathy, and poor self-care behaviors were associated with DFU [4].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Zhang et al reports that there are certain demographic factors associated with increased odds of 30-day readmission, such as female sex, black race (vs. white), older age, and others (Zhang et al 2021). There are some studies that claim there is no difference between genders, such as the study by Goodridge et al that reports that between unhealed and healed ulcer groups, there were no significant differences in gender distribution, age, and general health self-rating (Goodridge et al 2005), and a study by Salameh et al reported that there are no differences between DFU and non-DFU groups in terms of gender, as well as other factors (Salameh et al 2020). Regarding marital status, Pedras et al analyzed that almost all patients were married, and the main caregiver reported being the patient's spouse or an offspring.…”
Section: Gender Variables and Diabetic Footmentioning
confidence: 99%
“…Stress and suicidal tendencies are possible consequences of the chronicity of this condition (Goodridge et al 2006;Iversen et al 2015). Neuropathy, which is associated with poor glycemic control and is considered a risk factor for DFU, together with angiopathy, is a determinant of a low grade of mobility (Korzon-Burakowska and Dziemidok 2011; Perrin et al 2019;Lo et al 2021;Salameh et al 2020;Rerkasem 2011;Meijer et al 2001;Fejfarová et al 2014). Some conditions determined by low compliance with glycemic control are considered important risk factors, such as retinopathy (Lo et al 2021;Al Ayed et al 2020;Elkhider et al 2021), foot sensory loss (Salameh et al 2020), and nephropathies (Lo et al 2021;Salameh et al 2020;Elkhider et al 2021).…”
Section: Medical Consequences and Diabetic Footmentioning
confidence: 99%
See 1 more Smart Citation
“…Çalışmaya katılan hastaların eğitim durumları incelendiğinde büyük çoğunluğunun ilk-ortaokul mezunu olduğu görüldü (%80.8, n=63). Farklı ülke ve hastanelerde yapılan benzer çalışmaların bir kısmında eğitim seviyesi daha düşük olan popülasyonda ayak bakımı konusundaki bilgi seviyesinin daha düşük olduğu bildirilmiştir [13][14][15]. Başka bir çalışmada ise hastaların eğitim seviyesinin artmasıyla DM hakkındaki bilgi ve davranış puanlarının arttığı, benzer şekilde ayak bakımının da arttığı bildirilmiştir [11].…”
Section: İstatistiksel Analizunclassified